A character building effort for students in Barokah Nandan Sukoharjo Boarding School through three success programs: Alim faqih, Akhlakul karimah and Mandiri - Alfian Ubaidillah Alfauzi; Siti Choiriyah (UIN Raden Mas Said Surakarta, 2021)
Most of the students in Islamic boarding schools know the knowledge but do not implement it in daily life due to a lack of akhlakul karimah awareness. Based on this, a study aims to describe and analyze the implementation of the Three Success program in building the students' characters. Three Success program is a Â special program in Pondok Pesantren (Islamic Boarding School) Barokah Nandan Sukoharjo which consists of Alim Faqih, Akhlakul Karimah and Mandiri (Religious, Noble, and Independent). This research was a descriptive qualitative study. The subjects were Staff of Students Affairs, Students, and Ustadz (teachers) in the boarding school. The data collection was conducted by observation, interview, and documentation. To determine the validity of the data, the researcher used triangulation of methods and triangulation of sources. The data were analyzed using interactive data analysis with the procedure as data collection, data reduction, data display, and conclusion. The study results conclude that the implementation of the Three Success program was carried out by inviting students to participate in the activities within the program. This study contributes in overcoming the problem of studentsâ€™ characters deviation in Islamic boarding school and as an effort to enrich the knowledge in the education field, especially those related to the character building of Islamic boarding school students.